Agritourism as a form of supportfor individuals with autism spectrum disorder - Roman, Michał; Pasek, Marcin; Szczucka, Ewa; Zuzda, Jolanta (Turystyka i Rozwój Regionalny, 2025)
Rural tourism can support autistic individuals through sensory-friendly settings,animal contact and nature-based activities that promote self-regulation, social interactionand sensory integration. Within health-oriented tourism, animal-assisted services offerflexible, goal-directed engagement tailored to individual needs. This article presentsa case study of an inclusive agritourism facility in the Lubuskie region of Poland, illustratinghow agritourism can combine therapeutic, educational and ecological functions.The study highlights the role of nature and animal interaction in enhancing emotionalbalance, communication and wellbeing for individuals on the autism spectrum. Findingsindicate the strong therapeutic potential of rural environments and emphasise the shortageof Polish facilities adapted to neurodivergent visitors, pointing to the need for broaderimplementation of agrotherapeutic tourism practices.